MULTILINGUALISM AND LANGUAGE ATTITUDE THE “CAMEROONIAN PARADOX” - Hodieb, Liliane (Ideação, 2020)
The colonial past of Cameroon has serious consequences on its present, positive as well as negative. As a positive consequence, French-English bilingualism is perhaps the most noteworthy, resulting from the shared governance of the colony between France and Britain. However, while the British administration adopted the ‘Indirect rule’, the French colonists were led by a policy of assimilation which aimed at turning the colonized people into French individuals, particularly in their mind and education. This process involved relegating the numerous indigenous languages (about 250 in Cameroon) to the background, for the benefit of the French language whose prestige was high enough to subjugate Cameroonians. Thus, parents gradually ceased to pass down their language to their children. The younger generations, therefore inherited French as their mother tongue, but now they feel the need to recover their lost inheritance, i.e., indigenous languages. This is what we call here the “Cameroonian paradox”. This paper presents the results of a sociolinguistic survey of 32 Cameroonians living in France. The Postcolonial theory helps us understand this paradoxical phenomenon while raising issues of identity and language endangerment.